The gender gap in Italian medicine - De Simone, Silvia; Podda, Daiana; Lampis, Jessica (La Medicina del Lavoro, 2015)
Background: This study is collocated in the debate about the gender gap in Medicine giving voice to female physicians who have damaged the “glass ceiling”. Objectives: Our research offers a contribute to the exploration about the motivations of persistence of gender gap in Medicine despite current changes. Methods: This study is based on 21 biographical interviews to female physicians who are managers in Italian hospitals. The themes emerged by data analysis concerned the participants ’discrimination experiences in their hierarchical advancement, the evidences of a persistence of horizontal segregation in some medical specializations, the difficult to find a work-life balance and the effects of this difficult on the female physicians’ health. Results: Our research confirmed a persistence of gender gap in the medical world, which disadvantages women in their career choices and in their hierarchical advancement and which appears in the form of invisible barriers impregnated of stereotypes and prejudices that are taken for granted by many men and women, especially those who have the power; these barriers make the female doctors ‘health more vulnerable to the event of work-related stress. Conclusions: By the dates emerged the necessity of cultural and institutional interventions, actions for deconstruction of gender stereotypes, and the necessity of intervention for a more flexible and functioning work organization that satisfies the female physicians’ needs.